Amount of Vocabulary Required to Grasp Comprehension in a Text - Albaqshi, Jalal H. (Advances in Social Sciences Research Journal, 2020)
This study addresses the relationship between vocabulary and reading comprehension and Showing some other factors which affect the comprehension beside vocabulary. A descriptive analysis and correlation test were applied to show why some L2 learners cannot understand a gist of a text though they are familiar to many vocabulary. The sample group in this study consisted of 64 male Saudi learners. They were between the ages of 18 to 22 years old and had been studying English in formal settings for six years in the form of moderate doses of input but not intensive English. This study highlights the percentage coverage of vocabulary in a text rather than the whole learners ‘reservoir of vocabulary in order to understand the general ideas of a text. Results show that L2 learners need to be familiar at least with 62% to 71% of vocabulary in a text to grasp the gist of whole passage. This result helps to write down several implications for researchers and teachers of English as a second and foreign language.